Dysphagia in Myositis: A Study of the Structural and Physiologic Changes Resulting in Disordered Swallowing. (May 2020) - Azola, Alba; Mulheren, Rachel; Mckeon, Genevieve; Lloyd, Thomas; Christopher-Stine, Lisa; Palmer, Jeffrey; Chung, Tae Hwan
Abstract : Objectives: Dysphagia in patients with myositis is associated with an increased risk of aspiration pneumonia. However, the pathophysiology of dysphagia is poorly understood. The aim of this study was to understand how myositis affects swallowing physiology on videofluoroscopic swallow study. Design: This is a retrospective review of video fluoroscopic swallowing studies on 23 myositis patients with dysphagia from 2011 to 2016. Swallow studies were analyzed by timing of swallowing events and duration of swallowing events, diameter of upper esophageal sphincter opening, Modified Barium Swallow Impairment Profile, and Penetration-Aspiration Scale. The outcome measures for patients were compared with an archived videofluoroscopic swallow study from healthy, age-matched participants by Wilcoxon rank-sum tests. Results: Patients with myositis had a shorter duration of upper esophageal sphincter opening ( P < 0.0001) and laryngeal vestibule closure ( P < 0.0001) than healthy subjects. The diameter of upper esophageal sphincter opening did not differ between groups. Patients with myositis presented with higher scores on the MBSIMP than healthy subjects, indicating great impairment particularly during the pharyngeal phase of swallowing, and a higher frequency of penetration and aspiration. Conclusions: Dysphagia in patients with myositis may be attributed to reduced endurance of swallowing musculature rather than mechanical obstruction of the upper esophageal sphincter. Abstract : Supplemental digital content is available in the text.